2004
DOI: 10.1111/j.1936-4490.2004.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Dimensionality of Should and Will Service Expectations

Abstract: This study is a step forward in the continued evolution of our understanding of multiple standards of customer service expectations. By developing a higher‐order factor model, we examine the existence of hypothesized functional and technical dimensions of should and will expectations, and determine the causal relationships between the two types of expectations and the two hypothesized dimensions. In an effort to provide a richer conceptualization of should and will expectations, we test their dimensionality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Marketing researchers have distinguished between technical and functional attributes (Laroche, Kalamas, Cheikhrouhou, & Cézard, 2004). Technical attributes are concerned with outcomes or what is delivered or received as a result of product performance (e.g., product reliability).…”
Section: Lankton and Mcknight / Examining Two Edt Modelsmentioning
confidence: 99%
“…Marketing researchers have distinguished between technical and functional attributes (Laroche, Kalamas, Cheikhrouhou, & Cézard, 2004). Technical attributes are concerned with outcomes or what is delivered or received as a result of product performance (e.g., product reliability).…”
Section: Lankton and Mcknight / Examining Two Edt Modelsmentioning
confidence: 99%
“…The affective expectation model (AEM, [74]) asserts that how much a person thinks they will like an experience (affective expectation) is as important as what actually happens during the experience in the determination of how much the experience is enjoyed (affective reaction). Affect expectations relate to emotional attributes such as anger or joy [41]. Frontline employees in service recovery are in the negative mood with the negative affective expectation of customers and in turn display the hostility.…”
Section: A Customer Complaint and Service Provider Hostilitymentioning
confidence: 98%
“…Consumers' evaluations of an exchange or a transaction are based on what they expect will happen (i.e., predictions), what they expect should happen (i.e., norms or desires), and, after the transaction, what they perceive to have actually happened (Boulding et al 1993;Zeithaml, Berry, and Parasuraman 1993). Several empirical studies have demonstrated the distinctiveness of normative and predictive expectations and highlighted the importance of distinguishing between these two types (Boulding et al 1993;Laroche et al 2004). Tse and Wilton (1988) demonstrate the simultaneous influence of both predictive and ideal expectations.…”
Section: Theoretical Perspective Expectationsmentioning
confidence: 99%
“…In early work on service quality, expectations were defined as what consumers want or desire—in other words, what service firms should offer (Parasuraman, Zeithaml, and Berry 1988). In a more precise definition of the concept, should expectations correspond to the level of service performance buyers believe an excellent service provider can and should deliver (Laroche et al 2004).…”
Section: Theoretical Perspectivementioning
confidence: 99%